(untitled) (International Journal of Mass Communication, 2025)
In an interconnected world, global challenges like climate change transcend borders, complicating governance as national interests often clash. Unregulated information flows fuel misinformation and erode trust in institutions. Today’s governance resembles a complex puzzle, where addressing one issue may exacerbate another. The rise of e-commerce has transformed consumer purchasing behaviors and research, yet marketing lags in adapting to this shift, focusing on digital media rather than engaging consumers. This paper investigates how societal narratives and digital engagement can guide governance and marketing in a complex, interconnected world where trust in traditional institutions is declining. It introduces the Virtual Living Lab (VLL), a tool that analyzes social media, Big Data, and AI to track emerging public priorities and behavioral patterns. Research conducted in Japan and the UK during the COVID-19 pandemic reveals that well-being narratives play a vital role in shaping societal recovery and resilience. The findings emphasize that effective engagement requires not only relevant content but also emotional and contextual awareness, especially in times of uncertainty. As public perceptions of Well-Being evolve, particularly in Japan, organizations must ensure their messaging remains emotionally resonant and contextually relevant to foster behavioral change and promote healthier, more sustainable lifestyles.